Current Researches in Educational Sciences VI - Palabıyık, Ersin; Olgun, Yunuscan; Piştav Akmeşe, Pelin; Keçili, Bayram; Ergül, Ebru; Erşen, Zeynep Bahar; Esen, Yasemin; Yıldız, Hasan (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
Based in Ankara in Turkey, the independent academic publisher, Akademisyen Publishing House, has been publishing books for almost 30 years. As the directors of Akademisyen Publishing House, we are proud to publish around 2700 books across disciplines so far, especially in Health Sciences. We also publish books in Social Sciences, Educational Sciences, Physical Sciences, and also books on cultural and artistic topics. Akademisyen Publishing House has recently commenced the process of publishing books in the international arena with the “Scientific Research Book” series in Turkish and English. The publication process of the books, which is expected to take place in March and September every year, will continue with thematic subtitles across disciplines